PENINGKATAN MUTU SKL SISWA SMK MELALUI MODEL YANG BERORIENTASI PADA KEMAMPUAN PERANCANGAN DAN MELAKUKAN EKSPERIMEN UNTUK MELATIH KETRAMPILAN BERPIKIR KRITIS - Maimunah, Siti Annijat (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2017)
The legislation System of national education No. 20 Year 2003 about education standards consist of standard content, processes, the competence of graduates, educational personnel, infrastructure, management, financing and assessment of education.Standards of competence and standard of graduates, Graduates in Vocational secondary schools are expected to have the ability to build Standard and competence of graduates of the creative, and innovatively in decision making. The reality of the situation of vocational high school graduates do not meet the standard of competence of Graduates, because the existence of limited practical tools so that the experiment also rarely do. The purpose of the study is to describe the practicality, and the effectiveness of the implementation of the model of learning ability-oriented design and conduct experiments to practice critical thinking skills of students of SMK.As for the approach of this study is a descriptive qualitative. Based on the results of the implementation of the developed learning the real device, it can be concluded that the ability of the design-oriented learning and experimentation to train creative and critical thinking skills a valid, practical, effective, and can enhance critical thinking skills and creative as well as achieving perfection results of student learning. Positive student response after follow learning by applying the learning ability-oriented device design and perform experiments to practice critical thinking skills and creative students.Â Key words: quality improvement of the standard of competence of graduates of vocational high school Students, the ability of Designing and performing experiments, Thinking Skills